Developing Software for Village Financial Management Through the Implementation of Law No. 6 Year 2014 in the Direction of "Good Village Governance" - Handayati, P; Djuliardi, D; Restuningdyah, N; ., Vega; Mentari, S (KnE Social Sciences, 2018)
The national development planning system is known as a unity of development planning procedures that will result in long-term, medium-term and year-long development undertaken by state and community-level providers at the central and regional levels. Implementation of autonomy for the village will be a power for the village government to administer, manage and administer its own household, as well as increase the burden of village responsibilities and responsibilities, yet the implementation of the government should still be accounted for. Accountability in question is responsible for the management of village budgets. For now the common obstacle felt by most villages is related to the limitations in village finances. Often the Village Revenue and Expenditure Budget (APBDes) is not balanced, between receipts and expenditures. Such facts are caused by four major factors (Hudayana and FPPD, 2005). First: the village has a small revenu and its source of income is very dependent on very little aid. Second: village people’s welfare is low. Third: the low operational funds of the village to run the service. Fourth: that many development programs enter the village, but only managed by the service. The purpose of this study is to develop village financial management software implementation of Law no 6 2014 to realize Good Village Governance. This village finance software will accommodate in detail the tax calculations to be paid by the village treasurer. Keywords: Village Financial Management, Good Village Governance